A feminist critical discourse analysis of gender norms on Chinese social media: Empirical insights from WeChat public accounts - Qingqing Tang; Xin Zhang; Taixuan Liu (PLoS ONE, 2026)
This study examines how gender norms are expressed and negotiated in WeChat Public Accounts using Feminist Critical Discourse Analysis (FCDA). We built a sampling frame of the ten most active gender-related accounts (June–December 2023) and screened 359 posts for relevance and analyzability. Twenty-two articles were selected for close reading. Two researchers independently coded clause- and sentence-level segments and reached agreement through discussion. Coding followed six dimensions used throughout the paper: lexical choice, modality, intertextuality, voice positioning, affective tone, and strategic silence. Four recurring themes were identified. (1) Maternal discourse and gendered discipline: texts often link women’s value to motherhood and domestic duties, combining moral language with advice on correct behavior. (2) The body and mechanisms of shame: discussions of menstruation and sexuality frequently use medical or corrective language that assigns responsibility to individual women. (3) Gender identity in cultural, legal, and policy narratives: educational, media, and policy-adjacent texts describe ideal feminine roles through procedure, quantification, and role models, which stabilize familiar expectations. (4) Resistant discourses and incremental change: some pieces re-label practices, shift speaking positions, or use humor to push back against these norms. Overall, the analysis shows how everyday textual choices can normalize gendered expectations, while limited forms of resistance also appear. The findings are bounded by the small, purposive sample and the focus on text rather than audiences or algorithms. The study provides a transparent description of patterns observed in the 22 articles and clarifies where and how resistance is articulated within them.